Occupational outlook handbook - United States. Bureau of Labor Statistics; JIST Works, Inc. (Indianapolis : Jist Publishing, 2010)
"The Handbook describes the job outlook over a projected 10-year period for occupations across the nation . . . Except for the three exclusive chapters by JIST Publishing, material in this publication is in the public domain.
"Developed by the U.S. Dept. of Labor" -- Cover, p. [1]
"Bulletin 2700" -- t.p.
"Exclusive to JIST Publishing's OOH: 'Green occupations ; The personality-career quiz: match your personality to OOH jobs' -- 'How educators, counselors, librarians, and business professionals can best use the OOH.' -- T.p.
Includes bibliographical references and index.
Keywords: Labor supply -- United States; Vocational guidance -- United States; Occupations -- United States; Employment forecasting -- United States; Job descriptions